Creative Dramatics as an Effective Tool in Contemporary Education: A Pedagogical Discourse - Okoronkwo, Samuel Okoronkwo Chukwu (Mediterranean Journal of Social Sciences, 2011)
Creative dramatics remains a relatively new and burgeoning phenomenon in contemporary education. It is an attemptto use drama for more functional purposes. This paper surveys the instrumentality of creative dramatics as a classroomexperience and as an effective educational tool in contemporary education. It carefully considers its meaning and implications,scope, aims and objectives as well as its values to the growth of the child in all development gamut; as well as the vital andinvaluable role of the teacher in permeating the world of the child to understand and assist him to master the realities of hissurrounding as he is being prepared for the real world and a better living in life.